Atividade antiulcerogênica de Ipomoea imperati (Vahl) Griseb (Convolvulaceae) - Miyahara, Maria Regina Mortatti (2008)
Ipomoea imperati (Convolvulaceae) is used in traditional medicine for the treatment of inflammation, swelling and wounds, as well as to treat pains after childbirth and for stomach problems. I. imperati showed that indole alkaloids and resin glycosides are the most common biologically active constituents in the Convolvulaceae. In previous studies, I. imperati inhibited the topical and systemic inflammation in a concentration-dependent manner. I. imperati had a significant inhibitory activity against phospolipase A2 enzyme from bee venom. This work evaluates the antiulcerogenic activity of I. imperati in acute and chronic gastric lesions. A histological study was also carried out to evaluate the preventive and healing actions of I. imperati in gastric ulcer model. In our study, Ipomoea imperati (200 mg/Kg-1, p.o.) prevented the formation of gastric lesions in 77,2 % (p<0.05) when compared with the negative control tween 80. The positive control, lanzoprazole, prevented in 85,6% the gastric lesions formation induced by ethanol (p<0.05). Therefore, the oral administration of Ipomoea imperati one hour before the ulcerogenic agent prevented the ulcer formation, conserving the citoprotection characteristics of the gastric mucosa and assuring the integrity of gastric glands and gastric fossets. The healing activity of I. imperati (200mg/kg-1, p.o.) evaluated in chronic ulcer experiments induced by the acetic acid, was 70% (p<0.05). The positive control, cimetidine, healed 78,8% of the gastric lesions (p<0.05). The histological analysis confirmed the recovery of the mucosal layer (gastric glands, gastric fossets and surface epithelium) and the muscle mucosal layer harmed by the acetic acid. It was observed that in vivo experiments confirmed the preventive and healing activities of I. imperati in the gastric mucosa, being these effects similar to commonly used antiulcerogenic drugs such as lanzoprazole and cimetidine. The results are confirmed by the morphological study carried out in our laboratory, where I. impereati preserved the characteristics of the gastric mucosal tissue of rats.